Modelos bayesianos para análise de características reprodutivas de fêmeas Nelore - Garcia, Diogo Anastácio [UNESP] (2014)
Reproductive traits are very important to beef cattle production system and, some of them, such as age at first calving (AFC), days to calving (DC), and longevity (LONG) are easy to measure and do not bring further measurement costs to the production system. However, these reproductive traits show low heritabilities and, one of the reasons might be the fact that only fertile females have phenotypic records, because when the genetic evaluation is performed some cows have missing records due to reproductive failure, as well as due to voluntary and involuntary culling, which are made before the breeding season, and, in some cases, due to inconsistent phenotypic informations. These partially or unobserved phenotypes are termed as censored records. According to some studies, properly accounting for censored records in genetic analysis could avoid distorted inferences and better genetic breeding value predictions. Several methodologies have been proposed to cope with censored records in genetic evaluations, such as models in which censored records are penalized, Bayesian hierarchical models to deal with censored data, threshold-linear models, and frailty survival models. However, these approaches have not been widely applied in Brazil. The objectives of this study were to evaluate age at first calving, days to calving, and longevity, of the Nellore breed females, applying models which handle phenotypic informations as uncensored and censored, aiming to find appropriate models to genetic evaluation for these traits. Data were provided by Nellore Alianca and reproductive records of animals born from 1993 to 2007, in farms located in south-east and middle-west of Brazil, were considered in the study. Contemporary groups (CG) for AFC were defined by the combination of farm, month, and year of birth, farm and management group at weaning, and farm and management group at long-yearling. For DC and LONG ...